Feminists building peace and reconciliation: beyond post-conflict. (3rd May 2016) - Porter, Elisabeth
Abstract: Many feminists find the concept of 'post-conflict' troubling for two main reasons. First, the discursive space of post-conflict is contestable with fuzzy lines around when the conflict period becomes post-conflict. Second, for women, the period following the cessation of armed aggression continues to be one of insecurity, where intimate partner violence often remains high, particularly when male ex-combatants return from fighting. In the so-called post-conflict period, a culture of gendered violence, gendered insecurity and militarisation remains. I argue that the transition from conflict provides opportunities for transformation from a culture of violence to one of peace, from insecurity to security and from antagonism to reconciliation. This article outlines a four-fold conceptualisation of reconciliation as a spectrum, reconciling relationships, processes and cultures of reconciliation. To move beyond gender-blind notions of post-conflict, the article seeks to decipher what is uniquely feminist about these ideas in affirming feminist peacebuilding and reconciliation.